9/9/90- in tribute to Bronislaw Zelek - Panayides, Angelos (My University, 2025)
Two years ago, Małgorzata's Bartosik book Bronisław Zelek. In the Letter Wonderland was published. It was created from the ground up – driven by a deep passion and fascination with his work, with the involvement of many people. This publication was made possible thanks to a successful Kickstarter campaign that was supported by nearly 300 people from several countries. This year, Zelek would have celebrated his 90th birthday. To mark this occasion, she organizied an exhibition titled “9/9/90” – a presentation of nine original posters by Zelek, along with nine contemporary reinterpretations of these works, created by exceptional artists from around the world, as a celebration of his 90th birthday. I hope this project will become a form of visual dialogue – a modern perspective on his work, which continues to inspire, even after all these years. It is a natural continuation of my book and another step in bringing this extraordinary figure back into the public eye. The exhibition is planned was a satellite event of Typolub 2025
Keywords: Poster, Exhibition